2012
DOI: 10.1002/jpln.201000434
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate effects on photosynthesis, nutrient accumulation, and nodulation in glyphosate‐resistant soybean

Abstract: Previous greenhouse studies have demonstrated that photosynthesis in some cultivars of first-(GR1) and second-generation (GR2) glyphosate-resistant soybean was reduced by glyphosate. The reduction in photosynthesis that resulted from glyphosate might affect nutrient uptake and lead to lower plant biomass production and ultimately reduced grain yield. Therefore, a field study was conducted to determine if glyphosate-induced damage to soybean (Glycine max L. Merr. cv. Asgrow AG3539) plants observed under control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 40 publications
12
83
3
2
Order By: Relevance
“…According to Ding et al (2011), glyphosate can provide a reduction in photosynthetic activity of the plant; thereby, lower production of photoassimilates also occurs. Moreover, the reduction of chlorophyll content, brought about by glyphosate application, can also lead to reduction in photosynthetic activity and therefore lower mass accumulation in the plant (Zobiole et al 2012). These characteristics were observed in the experiment with simulated rainfall, where plants with lower SPAD value had lower dry matter accumulation (Table 5).…”
Section: Resultssupporting
confidence: 51%
“…According to Ding et al (2011), glyphosate can provide a reduction in photosynthetic activity of the plant; thereby, lower production of photoassimilates also occurs. Moreover, the reduction of chlorophyll content, brought about by glyphosate application, can also lead to reduction in photosynthetic activity and therefore lower mass accumulation in the plant (Zobiole et al 2012). These characteristics were observed in the experiment with simulated rainfall, where plants with lower SPAD value had lower dry matter accumulation (Table 5).…”
Section: Resultssupporting
confidence: 51%
“…Several years after induction of GR crops, several studies indicated that glyphosate causes reduced levels of certain minerals, especially Mn and Ni, in GR crops (e.g., Zobiole et al, 2010Zobiole et al, a,b,c, 2011aZobiole et al, , 2012Bellaloui et al, 2009;Bott et al, 2008). Most of these studies were conducted in greenhouse and have been used as support for claims of decreased yields and other adverse effects of glyphosate on GR crops (e.g., Huber, 2007;Johal and Huber, 2009).…”
Section: Glyphosate-resistant Crops and Mineral Nutritionmentioning
confidence: 98%
“…Glyphosate (N-phosphonomethylglycine) is an herbicide that reduced nutrient uptake and shoot biomass of glyphosate-resistant soybean under field conditions in relation to rate and growth stage (Zobiole et al 2012). Glyphosate uptake by plants increased with the orthophosphate concentration in the soil (Denis and Delrot 1993).…”
Section: Farm Management Practicesmentioning
confidence: 99%